Electronically tunable voltage-mode quadrature oscillator based on high performance CCCDBA - Khateb, Fabian; Jaikla, Winai; Kubánek, David; Khatib, Nabhan (My University, 2013)
This paper presents a new electronically tunable voltage-mode quadrature oscillator using two high performance current controlled current differencing buffered amplifiers (CCCDBA), two capacitors and single resistor, all of them are grounded which is advantageous for monolithic integration. The condition of oscillation and the frequency of oscillation are independent and can be controlled by two separate bias currents. The output voltages are obtained at the terminals with aμmost zero internal impedances, thus there is no need to use any buffering devices. The MOS structure of the CCCDBA presented in this paper is of a high performance and ensures precision, large dynamic range, wide bandwidth and has the capability to drive a load with very low resistance. Non-ideal analysis of the proposed oscillator is provided and PSpice simulation results using the 0.18 μm n-well CMOS technology from TSMC are included to verify the correct functionality of the proposed circuit. © Springer Science+Business Media, LLC 2012.
Keywords: CCCDBA; CDBA; Quadrature oscillator; Voltage-mode applications